Determinants of Antenatal Care Visit Utilization of Child-Bearing Mothers in Kaffa, Sheka, and Bench Maji Zones of SNNPR, Southwestern Ethiopia - Abiyot Negash Terefe; Assaye Belay Gelaw (SAGE Publishing, 2019)
Background: Antenatal care (ANC) is a preventive obstetric health-care program aimed at optimizing maternal fetal outcome through regular monitoring of pregnancy. Even if World Health Organization recommends a minimum of 4 ANC visits for normal pregnancy, existing evidence from developing countries including Ethiopia indicates there are few women who utilize it due to different reasons. The purpose of this article is to identify determinants significantly influencing the ANC visit utilization of child-bearing mothers in the Kaffa, Sheka, and Bench-Maji zones of Southern Nation Nationalities and Peoples Region, Ethiopia. Methods: A total of 1715 child-bearing mothers were selected. Several count models such as Poisson, negative binomial, zero-inflated Poisson, zero-inflated negative binomial, hurdle Poisson, and hurdle negative binomial regression models were fitted to select the model which best fits the data. The parameters were estimated by maximum likelihood. Measures of goodness of fit were based on the Rootogram. Results: The data were found zeros (8.1%); the variance (3.794), which is less than its mean (3.91). Hurdle Poisson regression model was found to be better fitted with the data given. Variables are selected by backward selection method, through the analysis, zones, residence, age at first pregnancy, source of information, knowledge during danger sin, willingness, time of visit, and satisfaction, which were major predictors of ANC service utilization. The estimated odds that the number of ANC visits those child-bearing mothers made (mothers who lived in urban) are 3.52 times more likely than mothers who lived in rural keeping others variables constant and the like. Conclusion: Based on our findings, a lot of effort needs to be made by health offices to create awareness, maternal health-care programs should be expanded and intensified in rural areas, improve women's knowledge and awareness about the risk factor of late visit, the necessary investigations and follow-up throughout the antenatal period to promote regular attendance for ANC, and fulfill the client's satisfaction.